ANECDOTES AS ORGANIZATIONAL UNITS IN SCIENTIFIC RESEARCH - Umaralieva Dildora Takhirjanovna (Western European Studies, 2024)
Anecdotes, often dismissed as mere storytelling, possess a unique potential in scientific research, especially in qualitative studies. This article investigates the level of organization of anecdotes within scientific inquiry, drawing upon the works of F. Yoldosheva, B. Shamsiyeva, H. Yusupova, and U. Yoldoshev. Through qualitative analysis, we explore how these researchers utilize anecdotes as organizational units, shedding light on their role in enhancing the depth, context, and richness of scientific discourse
Keywords: Anecdotes; Scientific Research; Organization; Narrative Inquiry